Potensi Pelestarian Dan Pariwisata Rumah Pohon Suku Kombay Boven Digoel Papua - Yashinta Irma Pratami Hematang; Dina Limbong Pamuttu (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
The Treehouse is a work of Nusantara Architecture which is gaining in popularity in Papua, inhabited by two large Boven Digoel tribes namely the Korowai Tribe and also the Kombay Tribe. The Kombay Tree House is situated on a strong old tree with three layers of flooring, wooden walls and roofing material made of sago leaves. To assemble the house, a strong rattan rope is used. Behind that, Nusantara Architecture has a challenge that is accelerating development in the name of modernization. Behind modernization there are challenges for the preservation of the Tree House. For this reason, studies need to be carried out to explore the potential contained in the Treehouse so that the Treehouse should always be preserved. The purpose of this study is to analyze the categorization of the potential level of preservation of Treehouses using conservation criteria and explore the potential of tourism types of Treehouses. The results showed Treehouses have a category of high level of potential conservation. For tourism potential that can be further developed are educational tourism, nature tourism, and cultural tourism. This research is inductive exploratory research using descriptive-analytic survey method with observation and interviews also evaluative method.